MENINGKATKAN HASIL BELAJAR LOMPAT JAUH SISWA KELAS V SDN MAMAJANG I MAKASSAR MELALUI METODE BERMAIN - Karim, Achmad (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is a classroom action research conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. This study aims to improve the long jump learning outcomes of students at SDN Mamajang I Makassar using a pair-based model. The subjects in this study were 30 students at SDN Mamajang I Makassar. Based on the research conducted, it can be concluded that the application of a play-based model can improve the long jump learning outcomes of students at SDN Mamajang I Makassar. The results of data analysis indicate a significant increase in the long jump learning outcomes of students at SDN Mamajang I Makassar. In cycle I, the long jump percentage of students at SDN Mamajang I Makassar was 53.33%, and increased to 100% in cycle II.